2020
DOI: 10.1038/s41598-020-67502-8
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation exposure to cigarette smoke and inflammatory agents induces epigenetic changes in the lung

Abstract: Smoking-related lung tumors are characterized by profound epigenetic changes including scrambled patterns of DNA methylation, deregulated histone acetylation, altered gene expression levels, distorted microRNA profiles, and a global loss of cytosine hydroxymethylation marks. Here, we employed an enhanced version of bisulfite sequencing (RRBS/oxRRBS) followed by next generation sequencing to separately map DNA epigenetic marks 5-methyl-dC and 5-hydroxymethyl-dC in genomic DNA isolated from lungs of A/J mice exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 52 publications
(77 reference statements)
0
29
0
Order By: Relevance
“…By comparing the oxRRBS dataset with RRBS datasets, an accurate 5hmC fraction can be calculated ( Figure 2 A). Previously, we successfully employed this approach to characterize methylation and hydroxymethylation changes in an animal model of lung cancer (A/J mice treated with lipopolysaccharide) [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By comparing the oxRRBS dataset with RRBS datasets, an accurate 5hmC fraction can be calculated ( Figure 2 A). Previously, we successfully employed this approach to characterize methylation and hydroxymethylation changes in an animal model of lung cancer (A/J mice treated with lipopolysaccharide) [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the murine IBD model with significant dysplasia and hyperplasia prior to solid tumor formation, these results suggest an early effect of DNA epigenetic marks on triggering altered expression of cancer-related genes. Our recent study involving a murine model of inflammation-induced lung cancer analogously revealed early epigenetic changes within tumor suppressor genes Rassf1, Cdh13, and Dapk1 [ 52 ]. Future functional studies will establish whether such epigenetic dysregulation directly contributes to initiation and progression of cancer.…”
Section: Discussionmentioning
confidence: 99%
“… 45 Exposure to toxicants, such as prolonged cigarette smoke inhalation, may influence biomarkers by having direct effects on the small airway epithelium (SAE). 46 …”
Section: Methodsmentioning
confidence: 99%
“…These studies are further corroborated by in vivo and translational studies. Mice intranasally exposed to inflammatory agent lipopolysaccharide (LPS) for two weeks reduced the global levels of cytosine hydroxymethylation (5hmc) in lung tissue [ 168 ]. Six weeks exposure to LPS increased cytosine methylation (5mc) in CDH13 (cell adhesion molecule), Ahrr, Tet1 and Rassf1 (tumor suppressors) and DAPK1 (pro-oncogene) which together highlight involvement of complex inflammatory stimulus involving methylation-based regulation of inflammation as well as tumor suppressors and oncogenes in progression of lung cancer.…”
Section: Epigenetic Regulation Of Inflammationmentioning
confidence: 99%